Reinterpretation of History in the Books of Chronicles: The Case of King Manasseh - Kinowski, Krzysztof (Collectanea Theologica, 2021)
Manasseh of Judah: an idolatrous ruler and murderer to be condemned, as depicted in 2 Kgs 21:1-18, or a converted sinner and restorer of his kingdom, a pattern to follow, as presented in 2 Chr 33:1-20? These two biblical portrayals of the king cannot be reconciled without raising questions about the assumptions of the biblical historiographers who built up two alternative traditions about this biblical figure. The case of King Manasseh is therefore an intriguing example of the Chronicler’s reinterpretation of historical material found in the Books of Kings. It is argued that particular narrative strategy and theological issues lie behind this vision of the king and its significance for the addressees of both writings. Consequently, the biblical figure of Manasseh is somehow biased, and its historical reconstruction has its limitations.